الصورة الفنية والأساليب اللغوية في رثاء الزوجة لدى (جرير_ديك الجن_البارودي) ــ دراسة أسلوبيةــ - أمين, أ.د. هيرش محمد; عبدلله, مهاباد جلال (Sulaimani Journal for Humanities, 2023)
As we know, rejuvenation has an important place in Arabic poetry, because it is one of the most important poetic purposes used by poets and writers, and rejuvenation as a type of rejuvenation explains aspects of family relationships. This research is about poets' rejuvenation of their spouses in ancient and modern times, so that we have taken a poet as an example in each era. The aim of our research is to know the ability to describe spouses Therefore, the title of our source is (Artistic Image and Linguistic Style) in the poems of rejuvenation of couples by Jarir, Wadik al-Jin and Baroodi We have done it with the poets as questions and repetitions. This study consists of an introduction, three parts and an ending, and we have chosen a stylistic approach to analyze our poetic stories. Finally, we have reached several conclusions that we have presented in a number of points, and we have concluded the study with a list of sources